Mobilização das inteligências múltiplas para a alfabetização científica em um contexto de atendimento para alunos com altas habilidades/superdotação - Fredo, Solange Cleia Bencke (2019)
This work is based on the concept of intelligence, based on Howard Gardner's Theory of Multiple Intelligences (TIM), an author who describes the existence of eight human intelligences. We articulate the Theory of Multiple Intelligences as a way to promote students' Scientific Literacy. The research was conducted with students participating in the High Skill / Gifted Multifunctional Resource Room. Thus, we also present Joseph Renzulli's Theory of the Three Rings, which seeks to define the individual with High Skills / Giftedness and the Whole-School Enrichment Model (SEM), which is a service proposal for students with High Skills / Giftedness. . We discuss the concept of Scientific Literacy (CA), giving greater emphasis to the structuring axes and indicators described by Sasseron, using them as drivers for this work. Thus, the development of a Didactic Sequence (SD), aimed at expanding Scientific Literacy with the theme “Waste, Society, Environmental Impacts and Energy Production - Biogas”, was evaluated in students who attend the Multifunctional Resource Room. Giftedness of a State College of a municipality of Western Paraná, through working with students who have different types of intelligences. During the application of the didactic sequence, we began each encounter with a guiding guiding question, in which the research subjects responded by demonstrating the concepts they already had about the subject. After this moment, we introduce the theme with the help of texts, videos, debates and a scientific research work. The discussions during the meetings were audio recorded for later analysis. At the end of each planned meeting the initial question was resumed and the students answered it again. We analyzed students' arguments for indicators that showed whether CA was happening. Regarding the Multiple Intelligences (MI) we seek to indicate which were most mobilized with the application of the didactic sequence through the process of observation and analysis of the data constituted throughout the research. Throughout the didactic sequence, we sought to mobilize the different intelligences, however, it was only possible to mobilize the Body-Kinesthetic Intelligence in the third learning focus. Regarding the work with the Scientific Literacy and the Multiple Intelligence Theory, we realized that with a diversified methodology that instigates and encourages the different intelligences, there was greater interest of the research subjects and the manifestation of a larger number of indicators of Scientific Literacy. As for the approximations between the scientific research work of the didactic sequence and the Enrichment Model for the whole school, we contemplate several similarities, such as investigative learning, knowledge expansion, planning, arguing, hypothesis and problem solving